2016
DOI: 10.1016/j.jhazmat.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission active tetraphenylethene-based sensor for uranyl ion detection

Abstract: A novel tetraphenylethene-based fluorescent sensor, TPE-T, was developed for the detection of uranyl ions. The selective binding of TPE-T to uranyl ions resulted in a detectable signal owing to the quenching of its aggregation-induced emission. The developed sensor could be used to visually distinguish UO2(2+) from lanthanides, transition metals, and alkali metals under UV light; the presence of other metal ions did not interfere with the detection of uranyl ions. In addition, TPE-T was successfully used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…However, their application for the detection or extraction of UO 2 2+ has not been explored. More importantly, the exploration of COFs for fluorescence detection of UO 2 2+ is still in its infancy, and most UO 2 2+ -sensing platforms are often hampered by poor selectivity and a long response time [37][38][39][40] .…”
mentioning
confidence: 99%
“…However, their application for the detection or extraction of UO 2 2+ has not been explored. More importantly, the exploration of COFs for fluorescence detection of UO 2 2+ is still in its infancy, and most UO 2 2+ -sensing platforms are often hampered by poor selectivity and a long response time [37][38][39][40] .…”
mentioning
confidence: 99%
“…In 2001, Tang et al reported a phenomenon called aggregation induced emission (AIE) with a propeller-shaped nonemissive organic molecule on dissolving with solvents forming emissive aggregates. The proposed mechanism suggests the curtailment of molecular rotations made possible with aggregate formation leading to reduction of non-radiative pathways [20,21]. Nanoaggregates were successfully employed in detecting nitroaromatics because of the selective aggregative responses provided by the conjugated compound [68].…”
Section: Sensing Mechanism and Mode Of Sensingmentioning
confidence: 99%
“…Among various applications, sensory application is dominating due to the emerging organic chemist skills on tuning the CPs functionalities and fine-tuning it to the desired applications. Various sensing mechanism and modes of sensing furnish unprecedented CCPs sensory responses with ultrahigh sensitivity and selectivity [20][21][22][23][24][25][26]. Huge no of analytes have been monitored with good sensitivity utilizing the high end instrumental techniques such as high performance liquid chromatography (HPLC), gas liquid chromatography (GLC), gel permeation chromatography (GPC), energy dispersive X-ray spectroscopy (EDS), inductive couple plasma-atomic emission spectroscopy (ICP-AES), UV-Vis, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–5 ] have satisfactory sensitivity and selectivity, but the need for expensive instrumentation, sophisticated sample pretreatments, and highly trained personnel limits the application for portable and on‐site detection. Towards portable and on‐site detection of uranium, great progress has been achieved in the development of colorimetry, [ 6,7 ] fluorescence, [ 1,8,9 ] and electrochemistry [ 10–12 ] techniques, and in seeking new uranium receptors, such as uranium‐specific DNAzyme, [ 13–15 ] complicated organic molecules, [ 16 ] peptides, [ 17,18 ] and so on. Among them, many colorimetry, fluorescence, and electrochemistry sensors have been developed based on uranium‐specific DNAzyme due to its high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%